Exploration Of Lampung Traditional Music In Efforts To Preserve Culture By Kulit Tipis Community In Bandar Lampung - Yulita, Birgita Iyona; Susetyo, Bagus; Sejati, Irfanda Riski Harmono (Jurnal Seni Musik, 2021)
Traditional music is one of the elements of culture keeping the continuity, dynamics, cultural identity and also becoming a vehicle for transmitting the cultural values inherited from generation to generation. This study aims to identify and describe the exploration of traditional music Lampung as an effort to preserve music culture by the Kulit Tipis community in Bandar Lampung. This research was conducted using qualitative methods. Data collection techniques used literature study, observation, interviews, and documentation studies. The results showed that there were efforts to preserve Lampung traditional music by Kulit Tipis community in Bandar Lampung, namely: (1) Collaborating traditional Lampung musical instruments with modern musical instruments or traditional musical instruments from other regions. (2) Making musical compositions from Lampung folk songs or modern pop songs today. (3) Performing musical exploration performances in various festivals, regular bands, and competitions in Lampung or outside the Lampung area. (4) Creating and uploading their video recordings of musical composition performances from the Kulit Tipis community through social media, such as YouTube.